Design of a miniaturized HF conical monopole - Jiang, Dan (2013)
HF antennas are typically very large in size due to its very long operating wavelength. The water loading miniaturization technique was researched in this paper. With the large permittivity difference between water and free space, the size could be reduced to 1/9 of the normal antenna size ideally speaking. However, the large permittivity of water could block the transmission of electromagnetic waves to free space. Because of the complexity of water characteristics, this loading method was seldom researched. This paper serves as a discovery process about the possible water-loaded structures and methods.